HUBUNGAN KETERAMPILAN MEMBACA PEMAHAMAN DENGAN KETERAMPILAN MENULIS RANGKUMAN SISWA KELAS VIII SMP NEGERI 11 PADANG - Melasari, Wenni; Abdurahman, Abdurahman; Arief, Ermawati (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2016)
ABSTRACTÂ This article was written to look at the relationship between of the silent reading skills and the writing skills to summary of the students of class VIII SMP Negeri 11 Padang. The data in this research was test score of the silent reading skills and test score of the writing skills to summary. The data were obtained through two types of tests, namely objective tests to measure the silent reading skills and test performance to measure the writing skills to summary. Based on the results of data analysis and discussion, it was concluded the following three points. First, the silent reading skills of students of class VIII SMP Negeri 11 Padang located on qualifications More than Enough (LDC) with the average value (75,48). Second, the writing skills to summary of students of class VIII SMP Negeri 11 Padang located on qualifications More than Enough (LDC) with the average value (75,66). Third, there was a relationship between the silent reading skills and the writing skills to summary of students of class VIII SMP Negeri 11 Padang at significant level of 95% with n-1 degrees of freedom, namely tarithmetic>ttable (30,75>1,68). Therefore, H0 is rejected and H1 accepted because the test results prove that tarithmetic> ttable.Â Kata kunci: hubungan, membaca pemahaman, menulis rangkuman